PENGAMALAN AKHLAK DAN KEPEMIMPINAN KEPALA SEKOLAH DASAR ISLAM DALAM PEMBENTUKAN SEKOLAH EFEKTIF - Supriyatno, Triyo (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
This article suggests that practically Islamic Ethics (Akhlak) of school leadership plays a central role in school improvement and effectiveness. Practically Islamic Ethics (Akhlak) is the ability to understand and manage akhlak nazari and akhlak amali in the self, teachers, staff and students. Three major aspects of practically Islamic Ethics (Akhlak), understanding (tafakkur), appreciation that includes muraqabah and muhasabah to enhance cognitive process and decision making, and practice about Akhlak Islam that include riyadhah is described. This article also discusses how practically Islamic Ethics (Akhlak) contributes to school effectiveness by focusing on elements of school leadership and standard of leadership competencies which include two aspects that is personality and social aspect.